Persistent Human Chorionic Gonadotropin After Methotrexate Treatment and an Emergency Surgical Procedure for Ectopic Pregnancy. Issue 3 (21st August 2015) - Kurt-Mangold, Michelle; Van Voorhis, Bradley J.; Krasowski, Matthew D.
Abstract : The case study is a 33-year-old white female with persistently elevated serum human chorionic gonadotropin (hCG) levels following methotrexate treatment and emergency surgery for ectopic pregnancy. At the time of the first methotrexate dose, the serum hCG concentration was 27, 995 IU/L. The laboratory was consulted 3.5 months after the surgery, because serum hCG levels had stopped declining and had leveled off to around 80 to 90 IU/L but with negative urine pregnancy tests. Laboratory studies ruled out heterophile antibody interference and hook effect by multiple methods including analysis by different serum hCG assays, treatment with heterophile antibody blocking agents, and dilution studies. Three additional doses of methotrexate over six months were required for serum hCG concentrations to decline to undetectable levels. This case illustrates challenges that may arise with serum hCG measurements in management of ectopic pregnancies. Close collaboration between the laboratory and clinical service is key for optimal patient care.